2021
DOI: 10.3390/su131810118
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Willingness to Pay for a Carbon Tax

Abstract: Addressing environmental issues has been a significant challenge. Malaysia is one of the fastest-growing countries in terms of economic, social, and land use development but high in CO2 emission rates. The introduction of a carbon tax is seen to reduce greenhouse gases emission (GHG), but the uncertain extent of implementation, based on economic theory, remains unknown. Hence, the current study’s objectives are to assess residents’ knowledge and attitude towards GHG. It is also to analyse the factors influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Such effects have been observed in past information experiments (Sturgis et al 2010). Since education on its own relates positively to general scientific attitudes (Bak 2001) Goh and Matthew 2021) as well as due to them having better intellectual processing abilities (Parisi et al 2012), giving more information on environmental taxes could result in a weaker information effect for less educated people. The counterhypothesis to H 2 can thus be summarised as:…”
Section: Information Effects Environmental Taxes and Educationmentioning
confidence: 70%
“…Such effects have been observed in past information experiments (Sturgis et al 2010). Since education on its own relates positively to general scientific attitudes (Bak 2001) Goh and Matthew 2021) as well as due to them having better intellectual processing abilities (Parisi et al 2012), giving more information on environmental taxes could result in a weaker information effect for less educated people. The counterhypothesis to H 2 can thus be summarised as:…”
Section: Information Effects Environmental Taxes and Educationmentioning
confidence: 70%
“…The questionnaire was adapted from previous relevant studies on carbon taxation, such as Goh and Matthew (2021) and Unni et al (2022). However, some modifications were made to fit the objectives of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [11] showed that the people in China naturally have negative perceptions of a carbon tax, and their negative sentiments worsen when they have low trust in the government. In Malaysia, the residents of Klang Valley were willing to pay a carbon tax and this willingness was significantly influenced by demographic factors, including gender, age, income, and education [60]. To date, no published study has examined the influence of trust in government toward public acceptability for carbon tax implementation in Malaysia nor evaluated the three predictors of trust in government-accountability, integrity, and competence-in developing countries.…”
Section: Public Acceptancementioning
confidence: 99%